Pengaruh Struktur Modal dan Ukuran Perusahaan Terhadap Nilai Perusahaan Property dan Real Estate yang Terdaftar di BEI Periode 2021-2022 - Khoiriyah, Nurul; Mawardi, M. Cholid; Junaidi, Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This study is to examine the effect of capital structure and company size on the value of real estate and property companies listed on the Indonesia stock exchange for the 2021-2022 period. This research was a quantitative research. This study uses the annual financials statements of property and real estate companies listed on the Indonesia stock exchange as a population. The method uses purpose sampling with a sample size 30 data units. The analysis technique uses multiple linier regression analysis. The result of this study indicated that capital structure has a positive effect on firm value, company size has a negative effect on firm value, and simultaneously all independent variable effect firm value.Keywords : Capital structure, company size, firm value.